2014
DOI: 10.1097/mao.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Report of Endoscopic Cochlear Implantation

Abstract: Endoscopic cochlear implantation may become a viable, safe, and feasible alternative to the standard open transmastoid approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Several studies in the literature have documented a transcanal endoscopic approach for cochlear implantation . Reported advantages of the transcanal endoscopic approach include avoidance of drilling the mastoid cavity, better visualisation of the round window area and safety of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the literature have documented a transcanal endoscopic approach for cochlear implantation . Reported advantages of the transcanal endoscopic approach include avoidance of drilling the mastoid cavity, better visualisation of the round window area and safety of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have documented a transcanal endoscopic approach for cochlear implantation. 3,8,9 Reported advantages of the transcanal endoscopic approach include avoidance of drilling the mastoid cavity, better visualisation of the round window area and safety of the facial nerve. However, in a recent study that analysed the orientation of the cochlear basal turn in relation to the ear canal, it was demonstrated that the trajectory provided by the conventional posterior tympanotomy aligned more favourably with the cochlear basal turn than the transcanal approach, thus may result in less damage caused by deflection of the electrode array in the scala tympani.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…An endoscope will provide a very detailed view of the round window niche and associated anatomy through the ear canal . There have been reports of endoscopic cochlear implant surgery that includes transcanal access and wiring . Reported advantages include better visualization of the round window area, avoidance of drilling the mastoid, and safety of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly at similar times, endoscopic cochlear implantation surgery was also reported, although it is a relatively new entity [15][16][17] . Hiraumi et al [17] reported transcanal endoscopic cochlear implantation in temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Hiraumi et al [17] reported transcanal endoscopic cochlear implantation in temporal bone. Dia et al [15] reported 25 cases of endoscopic cochlear implantation with an endoscopic transcanal technique from two different clinics. In this study, an electrode was inserted via a transcanal approach by an endoscope without mastoidectomy.…”
Section: Discussionmentioning
confidence: 99%